Analysis Of The Influence Of Leadership Style And Work Environment On Employee Loyalty Through Job Satisfaction at PT PLN (Persero) Up2d North Sumatra - Abdi Alfrido Pardosi; Elfitra Desi; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to explore the impact of leadership approach and working conditions on employee loyalty, using job satisfaction as an intermediary factor at PT PLN (Persero) UP2D North Sumatra. Quantitative methodology was used, specifically through survey techniques. Data were collected by distributing questionnaires to employees, and the results were evaluated using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that both leadership approach and working conditions have a positive and substantial influence on job satisfaction. In addition, job satisfaction and working conditions were also proven to have a positive influence on employee loyalty. However, leadership approach did not show a significant direct impact on employee loyalty. Examination of the indirect effect showed that job satisfaction acts as a mediator in the relationship between leadership approach, work environment, and employee loyalty. As a result, it can be concluded that job satisfaction plays a significant role in increasing employee loyalty. Therefore, PT PLN (Persero) UP2D North Sumatra should focus on improving leadership efficiency and fostering a better work environment to improve employee satisfaction and loyalty.